PENGEMBANGAN BAHAN AJAR MATEMATIKA BANGUN DATAR BERBASIS PROBLEM BASED LEARNING PADA SISWA KELAS III SEKOLAHD ASAR - Cindi Safitra Saragih (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study intends to analyze and test products from the development of teaching materials for mathematics flat shapes based on problem-based learning for third grade elementary school students, this study uses research and development methods (research and develop) with the 4D model (define, design, develop and disseminate), but researchers limit it only to the develop stage, namely limited product trials. The results of the study explained that the product that the researcher developed obtained the results of the validity test with an average of 0.80 and the practitioner test with an average of 0.92 with valid/worthy criteria used in the process of learning flat building mathematics. However, this research is not fully perfect so further development is needed.